Analisa Pengaruh Jumlah Urea Dan Holding Time Proses Powder Nitriding Terhadap Ketahanan Aus Material FC 25 - Umen Rumendi; Achmad Muhammad; Mohamad Gheo Wiriaputra (Jurnal Teknologi dan Rekayasa Manufaktur, 2019)
The advantages of FC 25 cast iron over steel: low-cost material, good castability, better vibration resistance and machinability. Reduction in the function of an engine component is 70% due to wear and tear (55%) and corrosion (15%). The powder nitriding process can increase the wear resistance of FC 25 material by increasing surface hardness by diffusing nitrogen atoms to the surface of the specimen at a temperature of 500-590°C. The powder nitriding produces a white layer consisting of the compound γ (Fe4N) and ε - (Fe2-3N) and has a high hardness. The influential variables are degree of availability (d.o.a) urea, holding time and temperature. Six variable variations were carried out, namely d.o.a 0,1 & d.o.a 0,2, at each holding time of 1.5, 2.5 and 3.5 hours, at a constant temperature of 550°C. The higher d.o.a urea and the longer holding time of the powder nitriding process, the white layer will be thicker and the specimens are more resistant to wear, so that this nitriding powder successfully increases the wear resistance of FC 25 material.